PKM Pemberdayaan Kelompok Perikanan Pengolahan dan Pemasaran (POKLAHSAR) Toengge Sejahtera Menjadi Sentra Ikan Teri di Kabupaten Kolaka - Masitah Masitah; Anti Landu; Doddy Ismunandar Bahari (Universitas Muhammadiyah Sidenreng Rappang, 2024)
The Toengge Sejahtera Processing and Marketing Fisheries Group (Poklahsar) is a productive economic fisheries group engaged in the production/processing of dried fish to improve the welfare and development of group members' resources. The Toengge Sejahtera group members are mothers who process and partially market anchovy products. The methods used in the production process are still traditional. However, in carrying out their business activities, partners are constrained in developing their products. Some of the priority issues of partners include 3 areas, namely the production field, the business management field, and the marketing field. The solution to this priority problem is product diversification which can improve the quality and quantity of partner business products so that it has an impact on sales interest. PKM aims to help partners develop their products through the diversification of processed anchovy products. The methods used in this activity are FGD, socialization, training, and evaluation of activities. The results of Community Service activities are an increase in partner skills and knowledge in hygienic anchovy production, processing anchovies into anchovy sauce, packaging anchovy-based fishery products by standards and increasing digital marketing.